Answer:
m = {-6, -4}
Step-by-step explanation:
Subproblem 1:
Set the factor '(6 + m)' equal to zero and attempt to solve:
Simplifying
6 + m = 0
Solving
6 + m = 0
Move all terms containing m to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + m = 0 + -6
Combine like terms: 6 + -6 = 0
0 + m = 0 + -6
m = 0 + -6
Combine like terms: 0 + -6 = -6
m = -6
Simplifying
m = -6
Subproblem 2:
Set the factor '(4 + m)' equal to zero and attempt to solve:
Simplifying
4 + m = 0
Solving
4 + m = 0
Move all terms containing m to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + m = 0 + -4
Combine like terms: 4 + -4 = 0
0 + m = 0 + -4
m = 0 + -4
Combine like terms: 0 + -4 = -4
m = -4
Simplifying
m = -4